SIMBOLISME PATUNG MACAN KURUNG JEPARA - Adisukma, Wisnu (Institut Seni Indoensia Surakarta, 2018)
The existence of Macan Kurung statue nowadays is very rare. If there is craftsperson or artisan who made it, there was very rare of them who certainly recognize the Macan Kurung statue symbolism. In this research, this statue is considered as artifact that contain of expression of self-representation which is constructed by instinctive culture. This expression was represented by object i.e. art of Macan Kurung statue and the meaning of statue appareance. The searching for meaning was the existence from artist concept, Asmo Sawiran and Singowiryo. This research was conducted to obtain tension qualified information. Therefore, this research used qualitative research method. The result showed the message of anti-colonialism value from this statue. Macan Kurung statue was also as counter culture appearance. This culture was wished for assemble Javanese culture legality as adiluhung and dynamic although foreign culture considered as modern culture entered in Javanese people.Keywords : Jepara, Macan Kurung, Symbolism